Upaya Mengatasi Bullying Melalui Layanan Bimbingan Kelompok Bagi Remaja Panti Asuhan ‘Aisyiyah Padang Panjang - Yani, Anisa Putri; A, Afrinaldi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Bullying, especially verbal bullying, is still common among adolescents. Adolescents living in orphanages are vulnerable to bullying. This is due to socioeconomic status, differences in family background, and low self-esteem. The impact of bullying for adolescents in orphanages is serious enough that it needs to be addressed immediately. One approach that can be taken is through group guidance services. Group guidance was chosen because it can provide social support and increase the self-esteem of victims of bullying. Through group guidance, adolescent victims of bullying can learn coping skills, such as assertive communication and problem solving. They can also share their experiences with fellow victims of bullying. Thus, it is hoped that group guidance services can reduce cases of verbal bullying and help adolescent victims of bullying in orphanages to have a stronger mentality in dealing with bullying.